2006
DOI: 10.1007/s00464-006-0041-4
|View full text |Cite
|
Sign up to set email alerts
|

The importance of symptom assessment in the surgical treatment of gastroesophageal reflux disease and Barrett’s esophagus

Abstract: The "art" and science of symptom assessment in the evaluation of patients with gastroesophageal reflux disease has been under emphasized. In fact, it is critical to judgements regarding surgical versus non-surgical therapy and is much more difficult than meets the eye. Many symptoms thought to be secondary to gastroesophageal reflux are not, and some, such as asthma cough and chest pain, which are commonly thought secondary to other causes, are indeed symptoms of reflux. Diagnostic studies are helpful but far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Autonomic NP with damage of efferent and afferent nerve fibers has been made responsible for this phenomenon and it was concluded that GERD questionnaires were not useful for diabetic patients [21]. However, one may criticize that both authors [11,21] used questionnaires which have not been validated and lack adequate reliability and responsiveness [22][23][24]. Similar results have been described for GERD symptoms in patients with DM type I, too [25].…”
Section: Gerd Related Symptomssupporting
confidence: 63%
“…Autonomic NP with damage of efferent and afferent nerve fibers has been made responsible for this phenomenon and it was concluded that GERD questionnaires were not useful for diabetic patients [21]. However, one may criticize that both authors [11,21] used questionnaires which have not been validated and lack adequate reliability and responsiveness [22][23][24]. Similar results have been described for GERD symptoms in patients with DM type I, too [25].…”
Section: Gerd Related Symptomssupporting
confidence: 63%